2008
DOI: 10.1103/physrevb.77.104402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of thermal entanglement in spin clusters using magnetic susceptibility measurements

Abstract: The present work reports an experimental observation of thermal entanglement in a clusterized spin chain formed in the compound Na2Cu5Si4O14. The presence of entanglement was investigated through two measured quantities, an Entanglement Witness and the Entanglement of Formation, both derived from the magnetic susceptibility. It was found that pairwise entanglement exists below ∼ 200 K. Tripartite entanglement was also observed below ∼ 240 K. A theoretical study of entanglement evolution as a function of applie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 37 publications
0
104
0
1
Order By: Relevance
“…In spite of that, it is fragile and can easily vanish due to the inevitable interaction of the system with its environment [4]; and due to this condition, it was thought that entanglement could only exist at low temperatures. However, recently, it has been shown that entanglement can also exist at higher temperatures, and can be detected through the measurement of some thermodynamic observables [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Abstract: Quantum Discord Geometric Correlations Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of that, it is fragile and can easily vanish due to the inevitable interaction of the system with its environment [4]; and due to this condition, it was thought that entanglement could only exist at low temperatures. However, recently, it has been shown that entanglement can also exist at higher temperatures, and can be detected through the measurement of some thermodynamic observables [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Abstract: Quantum Discord Geometric Correlations Molecularmentioning
confidence: 99%
“…In spite of that, it is fragile and can easily vanish due to the inevitable interaction of the system with its environment [4]; and due to this condition, it was thought that entanglement could only exist at low temperatures. However, recently, it has been shown that entanglement can also exist at higher temperatures, and can be detected through the measurement of some thermodynamic observables [5][6][7][8][9][10][11][12][13][14][15][16][17].Nevertheless, quantum entanglement does not encompass all quantum correlations in a system and recent studies have greatly expanded the notion of quantum correlations [18][19][20][21][22][23][24][25][26][27][28][29]; and the measure of quantum excess of correlations has been named as quantum discord [19][20][21]. In the last years, it was understood that quantum discord has an important role in many quantum information processing even without entanglement.…”
mentioning
confidence: 99%
“…Thermal entanglement was detected by both experimental [13,14,15] and theoretical [16] observations at low dimensional spin systems, formed in compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For spin systems can be used for gate operation in quantum computer thermal entanglement on solid spin systems have been widely studied, for example, the Heisenberg spin chain both in the absence [8] and presence [9,10] of an external magnetic field , spin rings [11] and spin clusters [12,13]. However, most of these works only focused on thermal entanglement between nearest, next-nearest or next-to-next-nearest neighbor spins [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these works only focused on thermal entanglement between nearest, next-nearest or next-to-next-nearest neighbor spins [14][15][16][17][18][19]. This motivate us to propose two questions: (i) Can thermal entanglement exist between distant non-nearestneighbor sites in spin system?…”
Section: Introductionmentioning
confidence: 99%